A new radiographic view of the hindfoot - Ikoma, Kazuya (BioMed Central, 2013)
BACKGROUND: A new radiographic view was proposed to evaluate the coronal plane alignment of the hindfoot under weightbearing conditions. METHODS: We studied 46 feet of individuals with normal appearing asymptomatic feet. On the antero-posterior roentgenogram using this new method, the line from the top of the sustentaculum tali to the lateral-inferior end of the posterior articular surface of the talus was obtained as the standard line showing varus or valgus of the calcaneus. We defined the angle between the longitudinal axis of the tibia and the standard line as described above as Varus-Valgus angle (V-V angle). RESULTS: The mean (±SD) V-V angle of the 46 feet studied was 76.4 (±3.6) degrees. CONCLUSION: The findings from this study indicate that it is possible to estimate the alignment of the hindfoot quantitatively by comparing individuals to the mean V-V angle that we calculated in our sample, which was 76.4 degrees.